Flooding of lands in the Volga region of Russia - Victor Vladimirovich Razumov; Eric Nikolaevich Molchanov; Natalya Viktorovna Razumova; Sergey Ivanovich Shagin (Наука. Инновации. Технологии, 2022)
On the basis of the analysis of extensive information on processes of flooding of lands in the territory of the Volga region of Russia provided in references and in materials of the official state reporting on a state and about protection of the surrounding natural and geological environment, use of lands, water resources, a condition of protection of the population and territories from emergency situations of natural and technogenic character, etc. data on the processes of continuous and temporary looding observed on lands of the studied region are for the first time systematized, the reasons of their emergence and development, scales and danger of manifestation in the territory of territorial subjects of the Russian Federation within the region are studied. The carried-out analysis has shown that in the territory of the Volga region the continuous flooding of lands connected with increase in level of underground waters as a result of natural and anthropogenous factors is widespread. Natural processes of flooding generally develop on the lands located near reservoirs in flood plains and on the nadpoymennykh terraces of the rivers, etc. Technogenic flooding of lands is generally dated for large settlements, located on plains and, generally connected with leaks from the water bearing communications, filling of reservoirs, violation of a superficial and underground drain at construction of roads, the industrial enterprises, etc. Steady and intensive rains and spring and aestivo-autumnal loods and high waters which almost annually happen on the territory of the region lead to temporary flooding of extensive territories of the region and often cause signiicant damage to the population and economy.